2002
DOI: 10.1098/rstb.2002.1071
|View full text |Cite
|
Sign up to set email alerts
|

No accident: genetic codes freeze in error–correcting patterns of the standard genetic code

Abstract: The standard genetic code poses a challenge in understanding the evolution of information processing at a fundamental level of biological organization. Genetic codes are generally coadapted with, or 'frozen' by, the protein-coding genes that they translate, and so cannot easily change by natural selection. Yet the standard code has a significantly non-random pattern that corrects common errors in the transmission of information in protein-coding genes. Because of the freezing effect and for other reasons, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 74 publications
1
51
0
Order By: Relevance
“…that the genetic code co-evolved to a point that it would have been too disruptive to change anymore (Crick, 1968;Sella and Ardell, 2006), so its evolution was stopped prematurely. 2. that it is not completely an accidental code in that it is indeed an error-correcting code better than a large number of competitors (Ardell and Sella, 2002) 3. that at some point in the past the codons were composed of 2 nucleotides only and the third nucleotide was acquired afterwards. This may be the reason why the natural code does not seem to be optimized for 3-codons and that almost all redundancies are in the third position (Sella and Ardell, 1973;Santos and Monteagudo, 2009).…”
Section: Resultsmentioning
confidence: 97%
“…that the genetic code co-evolved to a point that it would have been too disruptive to change anymore (Crick, 1968;Sella and Ardell, 2006), so its evolution was stopped prematurely. 2. that it is not completely an accidental code in that it is indeed an error-correcting code better than a large number of competitors (Ardell and Sella, 2002) 3. that at some point in the past the codons were composed of 2 nucleotides only and the third nucleotide was acquired afterwards. This may be the reason why the natural code does not seem to be optimized for 3-codons and that almost all redundancies are in the third position (Sella and Ardell, 1973;Santos and Monteagudo, 2009).…”
Section: Resultsmentioning
confidence: 97%
“…It has been convincingly shown that mistranslation in the first and third codon positions is more common than in the second position (Woese 1965;Kramer and Farabaugh 2007), but the transitional biased misreading in the second position is hard to justify from the available data. Ardell and Sella (2002) formulated the first population-genetic model of code evolution where the changes in genomic content of a population are modeled along with the code changes. This approach is a generalization of the adaptive concept of code evolution that unifies the lethal-mutation and translation-error minimization hypotheses and incorporates the well-known fact that, among mutations, transitions are far more frequent than transversions (Collins and Jukes 1994;Kumar 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This approach is a generalization of the adaptive concept of code evolution that unifies the lethal-mutation and translation-error minimization hypotheses and incorporates the well-known fact that, among mutations, transitions are far more frequent than transversions (Collins and Jukes 1994;Kumar 1996). Essentially, the Ardell-Sella model describes coevolution of a code with genes that utilize it to produce proteins and explicitly takes into account the "freezing effect" of genes on a code that is due to the massive deleterious effect of code changes (Ardell and Sella 2002). Thus, once the universal code was established, it became fixed and resistant to evolutionary changes.…”
Section: Discussionmentioning
confidence: 99%
“…We employ genetic code dynamics similar to that first introduced by Sella and Ardell (24)(25)(26). The main feature is the coevolution between the genetic code and codon usage at different functional sites.…”
Section: Diversification Of the Translation Mechanismmentioning
confidence: 99%